Lead exposures in older children (males and females 7–17 years), women of childbearing age (females 16–49 years) and adults (males and females 18+ years): FDA total diet study 2014–16. Issue 1 (2nd January 2020) - Gavelek, Alexandra; Spungen, Judith; Hoffman-Pennesi, Dana; Flannery, Brenna; Dolan, Laurie; Dennis, Sherri; Fitzpatrick, Suzanne
ABSTRACT: Dietary exposures to lead were estimated for older children, females of childbearing age and adults based on lead concentration data from the FDA's Total Diet Study and on food consumption data from What We Eat In America (WWEIA), the food survey portion of the National Health and Nutrition Examination Survey (NHANES). Estimated mean exposures varied based on the population and on the three different substitution scenarios for lead values below the limit of detection (non-detects = 0; non-detects = limit of detection; hybrid approach). Estimated mean lead exposures range from 1.4 to 4.0 µg/day for older children (males and females 7–17 years), 1.6 to 4.6 µg/day for women of childbearing age (females 16–49 years) and 1.7 to 5.3 µg/day for adults (males and females 18 years and older). Estimated 90th percentile lead exposures range from 2.3 to 5.8 µg/day for older children, 2.8 to 6.7 µg/day for women of childbearing age and 3.2 to 7.8 µg/day for adults. Exposure estimates suggest some older children may be exposed to dietary lead above the FDA interim reference level for lead in children of 3 µg/day. The results of this study can be used by the FDA to prioritise research and regulatory efforts in the area of dietary lead exposure.